A IMPLEMENTATION OF CHILDREN'S RIGHTS POLICY IN SOCIAL EDUCATION AT THE CLASS II PEKANBARU SPECIAL DEVELOPMENT INSTITUTE - Simanjuntak, Sriyunita (Mimbar Administrasi Mandiri, 2025)
This research is titled: Implementation of the Educational Rights of Students in Juvenile Detention at the Class II Special Guidance Institution for Children in Pekanbaru. This research was conducted at the Class II Special Guidance Institution for Children in Pekanbaru. The purpose of this research is to analyze the implementation of the policy on the educational rights of students in detention. The research results show that the implementation of the policy on the educational rights of students can be concluded that in terms of its execution, seen from the rights to worship and the right to education, the implementers have not fully complied with the policy because the SOP applied at the Special Guidance Institution does not cover the policies contained. Furthermore, in terms of supervising the implementation of the SOP for the guidance of juvenile detainees, the implementers have not fully understood their roles in carrying out the policy on the educational rights of students, so their roles in facilitating the educational rights of students have not been properly executed.